Peran Event Organizer dalam Mengaktivasi Kegiatan Wisata Desa: Studi Kasus Festival Bumi Bantaragung, Majalengka, Jawa Barat - Agoes, Adrian; Priscilla, Calista Joy (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2025)
This study analyzes the role of Event Organizers in activating tourism activities in Bantaragung Village, Majalengka Regency, West Java, through a case study of the 2024 Bumi Bantaragung Festival organized by Sauyunan Creation. Using a descriptive qualitative approach with case study design, data were collected through in-depth interviews, participant observation, and documentation studies. Findings reveal that the Event Organizer plays a central role across three critical stages: pre-event planning and knowledge transfer, during-event management and MSME activation, and post-event capacity building and infrastructure sustainability. Results indicate that Event Organizer intervention provides significant benefits economically through increased local MSME income, socio-culturally through preservation of local traditions, and organizationally through capacity transfer enabling independent village management. However, the study identifies challenges related to rapid social change and unequal distribution of economic impacts requiring continued assistance. This study contributes to community-based tourism literature by presenting a collaborative model among Event Organizers, financial institutions, and local communities that can be replicated for sustainable tourism village development in Indonesia.